Attached to monogamy? Avoidance predicts willingness to engage (but not actual engagement) in consensual non-monogamy. (March 2015) - Moors, Amy C.; Conley, Terri D.; Edelstein, Robin S.; Chopik, William J.
People view monogamy as the optimal form of partnering and stigmatize consensual non-monogamous (CNM) relationships. Likewise, attachment researchers often equate romantic love (and security) with sexual exclusivity. Interestingly, a sizeable minority of people engage in CNM and report high levels of satisfaction. Across two studies, we examined how individual differences in attachment were associated with attitudes toward CNM, willingness to engage in CNM, and current involvement in CNM. Among individuals who had never engaged in CNM, avoidance was robustly linked to more positive attitudes and greater willingness to engage in CNM. However, avoidant individuals were less likely to engage in CNM than in monogamous relationships. Understanding attachment in multiple partner relationships can provide new avenues for exploring the complexities of relationships.